2022
DOI: 10.1093/ofid/ofac277
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal and Histoplasma Antigen Screening Among People With Human Immunodeficiency Virus in Ghana and Comparative Analysis of OIDx Histoplasma Lateral Flow Assay and IMMY Histoplasma Enzyme Immunoassay

Abstract: Background Cryptococcal meningitis (CM) and disseminated histoplasmosis (DH) are common in people with HIV (PWH) and diagnosed by detecting cryptococcal antigen (CrAg) and Histoplasma antigen (Histo Ag) respectively. In Ghana, CM and DH are rarely suspected by clinicians due to limited epidemiological data. Methods This study was conducted among PWH in Ghana who are unwell. Sociodemographic and clinical data were collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…It is thus not surprising that despite the increasing cases of DH, GIH is rarely reported. Underreporting is surprisingly pronounced in Africa, a region known to have documented several cases of DH [ 4 , 6 , 125 , 126 , 127 ]. An extensive review on histoplasmosis in Africa that spanned seven decades identified 470 cases of histoplasmosis, of which only one case was reported with GIH [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus not surprising that despite the increasing cases of DH, GIH is rarely reported. Underreporting is surprisingly pronounced in Africa, a region known to have documented several cases of DH [ 4 , 6 , 125 , 126 , 127 ]. An extensive review on histoplasmosis in Africa that spanned seven decades identified 470 cases of histoplasmosis, of which only one case was reported with GIH [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review on histoplasmosis in Africa that spanned seven decades identified 470 cases of histoplasmosis, of which only one case was reported with GIH [ 5 ]. The paucity of data on GIH is first and foremost probably because histoplasmosis is still a neglected fungal disease in most parts of Africa, although with recent epidemiological studies, awareness is improving [ 125 , 126 , 127 ]. Recognition and reporting of GIH may also be hampered by a lack of adequate diagnostic procedures such as colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…It is the leading cause of morbidity and mortality in AIDS patients worldwide, affecting one million people annually [9,10]. The invasive form of the disease, cryptococcal meningitis (CM) kills more than 180,000 HIVpositive patients annually, with over 70% in low-income countries, including sub-Saharan African (SSA) countries [11,12]. Rare forms of extra-neuromeningococcal cryptococcosis exist in Africa [13].…”
Section: Cryptococcosismentioning
confidence: 99%
“…For example, a recently published study revealed that disseminated histoplasmosis may be more common than cryptococcal meningitis in Ghana contradicting the findings from the model study. 8 The few epidemiological studies are often spearheaded by foreign clinicians and the upskilled diagnostic capacity declines after the study. 9 , 10 Going forward, study investigators must engage policy makers and clinical leads towards drawing a framework for implementation and ensuring the integration of the research laboratory testing into clinical practice.…”
Section: Resultsmentioning
confidence: 99%